Utilization of Learning Technology in Strengthening Students' Prayer Education at MTs Teladan Ujung Kubu - Muhammad Asri; Sokon Saragih (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the implementation of instructional technology in strengthening prayer education for students at MTs Teladan Ujung Kubu, with a particular emphasis on its pedagogical impact on students’ cognitive understanding, practical accuracy, and worship awareness. Employing a qualitative approach through participant observation, in-depth interviews, and documentation, this research offers a contextual analysis of how digital learning tools are integrated into Islamic religious instruction. The findings demonstrate that the use of instructional technology such as audiovisual prayer simulations, digital prayer guides, and online religious learning resources significantly enhances students’ comprehension of prayer procedures, improves the precision of prayer movements and recitations, and increases students’ engagement in learning activities. The novelty of this study lies in its focus on technology-mediated prayer education at the madrasah level, highlighting how interactive and visual-based digital tools transform abstract religious instruction into concrete and experiential learning. Despite these positive impacts, the study identifies persistent challenges, including limited technological infrastructure, variations in teachers’ digital literacy, insufficient institutional support, and unequal student access to devices. Therefore, this study contributes to Islamic education discourse by emphasizing the need for systematic optimization of instructional technology to foster not only conceptual mastery but also internalized worship practices through contextual, interactive, and student-centered digital learning approaches.